Eksistensi Makanan Tradisional Kabuto pada Etnik Muna (Studi di Desa Lamaeo Kecamatan Kabawo Kabupaten Muna) - lisna yani; Rahmat Sewa Suraya; Shinta Arjunita Saputri (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The purpose of this study is to describe the process of making Kabuto for the Muna ethnic in Lamaeo Village, Kabawo District, Muna Regency, and to find out what types of preparations are made from Kabuto for the Muna ethnic in Lamaeo Village, Kabawo District. The form of this research is descriptive qualitative research using data collection techniques, conducting observations and interviews with the perpetrators of the creation of Kabuto and documentation. The informant determination technique used in this study was purposive sampling and used data analysis, data reduction, data presentation and conclusion drawing techniques. Based on the results of the research, it shows that: First, the process of extracting cassava (cassava), second, the process of peeling cassava (cassava), third, the drying process of cassava (sigkong), which has been peeled, for four days in a certain season. Fourth, the Kaghombo process, Cassava (Cassava) which has been dried in the sun for four days ago, is stored in a basket or sack along with Cassava (cassava) leaves as a cover on a certain side then stored above the attic as a fermentation process or for preservation of Kabuto, which is carried out in the morning. There are several ways of processing Kabuto, traditional food types in Lamaeo Village, Kabawo District, Muna Regency, such as Kantinibhera, Kaloli and Kantofi.